1981
DOI: 10.1246/bcsj.54.742
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Catalytic Decomposition of Hydrogen Iodide in the Magnesium–Iodine Thermochemical Cycle

Abstract: The decomposition of hydrogen iodide serves as the hydrogen-evolution step in several thermochemical water-splitting cycles, including the Magnesium–Iodine cycle. A kinetic analysis of the catalytic decomposition of hydrogen iodide has been carried out by the use of a flow method at 500–700 K. The platinum-supported active carbon catalyst (1 wt%) and the active carbon catalyst which have been found effective in the research reported previously, are used as the catalysts. The contact time-conversion relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…We consider previously reported equations for HI decomposition kinetics, both from Osawa over carbon and Pt/C catalyst [13] and from Shindo over Pt/␥-alumina catalyst [14], to be unsuitable for the description of our system, in that they cannot predict an increase in conversion with HI pressure, on the contrary they predict a decrease due to the raise of I 2 relative adsorption enhancing the backward reaction in respect to the forward one. In their models, each HI molecule followed an individual path, decomposing over the surface of the catalyst irrespective of the other molecules; in our model, the positive effect of the pressure means that a kind of cooperation among HI molecules shall be present, in that each HI molecule can be helped in decomposition by the already adsorbed ones.…”
Section: Kinetic Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…We consider previously reported equations for HI decomposition kinetics, both from Osawa over carbon and Pt/C catalyst [13] and from Shindo over Pt/␥-alumina catalyst [14], to be unsuitable for the description of our system, in that they cannot predict an increase in conversion with HI pressure, on the contrary they predict a decrease due to the raise of I 2 relative adsorption enhancing the backward reaction in respect to the forward one. In their models, each HI molecule followed an individual path, decomposing over the surface of the catalyst irrespective of the other molecules; in our model, the positive effect of the pressure means that a kind of cooperation among HI molecules shall be present, in that each HI molecule can be helped in decomposition by the already adsorbed ones.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…In the previous kinetic studies [13,14], only the iodine term has been considered, since it has been clearly demonstrated to be the most significant of all. We neglect, for the moment, only hydrogen adsorption term, surely the smallest one.…”
Section: Kinetic Analysismentioning
confidence: 99%
See 3 more Smart Citations